Design of mine-classified and graded short-message alarm system for message block prevention used in coal mine gas overrunning - LI Dongmei; SHAO Yanbin; ZHONG Yi; HU Xiaoyong; LI Wenjing (Gong-kuang zidonghua, 2014)
In view of problems that alarm message is sent without grade classification or only with grade classification but without mine classification, and short-message transmitting equipment is easy to stop working so as to cause message block in current short-message alarm for gas overrunning in coal mine, a mine-classified and graded short-message alarm system for message block prevention used in coal mine gas overrunning was designed. The system analyzes and processes data collected by digital remote monitoring system of coal mine gas, then classifies the data over alarm threshold according to different mine name and threshold level, and sends the data to mobile phone carried by corresponding mine and grade personnel through multi-interface short-message transmitting device with automatic reset function. The practical application result shows that the system improves ability of classification supervision and response of coal mine safety and reliability of safety management.